HIV-serodifferent couples' perspectives and practices regarding HIV prevention strategies: A mixed methods study - James M. McMahon; Janie Simmons; Amy Braksmajer; Natalie LeBlanc (Public Library of Science (PLoS), 2022)
A substantial proportion of heterosexually acquired HIV infections in the U.S. occur between partners in primary relationships characterized by mixed HIV status. The U.S. Centers for Disease Control and Prevention have issued guidelines prioritizing HIV-serodifferent couples for primary HIV prevention, including treatment-as-prevention and pre-exposure prophylaxis (PrEP). Yet, very little research has been conducted to understand the perspectives and practices of HIV-serodifferent couples regarding HIV prevention strategies in the U.S. To help fill this gap, we conducted a mixed methods study with 27 mostly Black/African American and Latinx HIV-serodifferent heterosexual couples residing in New York City to explore their knowledge, attitudes, practices, and perspectives regarding combination HIV prevention, including condoms, PrEP and viral control. All couples expressed the desire to maintain viral suppression in the HIV-positive partner, which was not always achieved. There was considerable heterogeneity in the use of HIV prevention methods by couples; and several patterns emerged that were largely driven by gender and relationship dynamics. Female partners, in particular, expressed high levels of anxiety around transmission of HIV and thus desired multiple methods of protection. Healthcare providers should consider couples' psychosocial well-being, relationship quality, and other motivational factors when helping to tailor HIV preventative care for mixed-status couples.